Curiosity and coincidentia oppositorum: on the legacy of Aleksander Sapieha as an author of Journey around the Slavic countries in the years 1802 and 1803 - Połczyńska, Magdalena (Poznańskie Studia Slawistyczne, 2018)
Aleksander Antoni Sapieha has gone down in the history of Polish science, he is one of the episodic figures in the political history of our country in the Napoleonic era; and in the history of Polish literature he appears as the author of the Enlightenment travelogue. The reading of Journey around the Slav countries in the years 1802 and 1803 and the semantically defined narrator-hero-real author on the basis of hermeneutic interpretation is an attempt to supplement the ways in which both, the travel book and its creator, are discussed in Polish scientific and popular science literature about those aspects that can be derived from the text itself. Among them, attention is paid to the specificity of a research attitude stretched, so to speak, between its two complementary pars, rational and idealistic, combined in a particular pragmatism of knowledge, in which the pursuit of cognition accompanies the pursuit of common good. The result of the hermeneutic experience of reading Sapiehaʼs travelogue is an attempt to capture his scientific and social heritage which takes into consideration the plane of this internally doubled, yet coherent research attitude, which in a broader sense seems to be surprisingly fresh and inspiring.